Julius Büdel und sein Konzept der Klima-Geomorphologie - Rückschau und Würdigung - Mensching, Horst (ERDKUNDE, 1984)
This contribution is an appreciation of Professor Julius Büdel, Würzburg, who died in August 1983. As a geographer and geomorphologist he was well-known far beyond the boundaries of German geomorphology. The development and significance of his concept of climatic geomorphology, within the framework of his work, is outlined and critically analysed. Between 1933 and 1983 with great perseverance, the necessary sharp-witted skill of scientific interpretation and brilliant imagination, J. Büdel developed his significant concept of climatic geomorphology. Throughout the years, this concept was continuously modified and adapted to the latest research results, without giving up the basic ideas. Simplified strongly, the basic concept is founded on the assumption that relief development is morphogenetically controlled by two main mechanisms that have produced two dominating generations of relief: excessive valley formation through the dynamics of frost action on the one hand and excessive planation in the marginal tropics on the other. Transition and transformation zones are found in between as connecting links. It is inevitable that such a simplified world model of climato geomorphological effectivity should entail shortcomings that are the result of a world-wide approach to the geomorphological development of the earth’s surface and the generalization of the very complex dynamics within and on the earth’s crust. Therefore, the concept of valley formation or planation, in a strict sense, is not the only concept possible. In his climato-geomorphological concept Büdel assigns decisive significane for the characteristics of even today’s relief to the formation of tropical peneplains, not only within the present tropical zone, but beyond it through to the subpolar zone. Although the Pleistocene cold climate processes of excessive valley formation have necessarily left only peneplain relics, these pene plains from a past tropical climate during the Tertiary are to have played the paramount role in the geomorphogenesis of all zones. With this concept of climatic geomorphology J. Büdel significantly inspired the science of relief development. His work encouraged and challenged numerous colleagues to participate in continuous discussion, critical investigation and further work in all climatic zones. In the future, further results in theory and field research will spring from this scientific confrontation with Büdel’s climato geomorphological work. Julius Büdel’s life-work thereby demonstrates its outstanding value.